MOTION APPEARANCE OF WOMEN IN THE MENSTRUAL AND ENDOMETRIAL CYCLE - Hadi, Santika Rentika (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2014)
In the endometrium and menstrual cycle, occurs several phase. Those are Menstrual Phase, Proliferative Phase, Secretaory Phase and Phase Ischemi. In the these phase occurs change in outpouring of sex hormones (estrogen and progesterone) that are closely related to the psychological condition (stress and emotions). Psychological conditions in these cycles is estimated to affect the appearance of human motion, appearance of motion in motor skills which means the ability to bring maximum results with spends certain minimum energy and time. The aim of this research was to reveal differences in the appearance of motion in the 200-meter run at the menstrual cycle and endometrium phase. Result of the statistical analysis showed that the appearance of motion in the form of 200-meter run in the fourth group of the menstrual phase, proliferative phase, secretory phase, and ischemic phase has no significant difference (P> 0.05). The conclusion of this research there was no differences in the appearance of motion (travel time to run 200 meters) in a woman in a state of menstrual phase, proliferative phase, secretory phase, and ischemic phase.